Leiomyosarcoma of the small intestine presenting as fever of unknown origin. Issue 3 (March 1992) - Dendale, P; Devis, G; Goossens, A
Abstract : We report a patient with a jejunal leiomyosarcoma who presented with fever of unknown origin. Resection of the tumour resulted in resolution of his symptoms.